APPLICATION OF THE CURRICULUM «SINSYS - KNAME" IN THE SYNTHESIS OF AUTOMATION - , С. М.; , А. Д.; , Н. П. (Municipal economy of cities (Technical science), 2013)
The problems of the synthesis of automation with a computer and modern software. On the example of the original program SinSys illustrated the possibility of studying the components of automation systems, training of existing models and real-automated equipment for municipal facilities.